2012
DOI: 10.1589/jpts.24.1087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Underwater and Overground Treadmill Walking to Improve Gait Pattern and Muscle Strength after Stroke

Abstract: Abstract.[Purpose] The objective of this study was to compare the effect of underwater and overground treadmill walking, which affect gait pattern and muscle strength in people with hemiparesis following a stroke. [Subjects] Twenty chronic stroke patients were included in this study.[Methods] The subjects were randomly allocated to one of two groups, the underwater treadmill walking (UTW) and overground treadmill walking (OTW) groups. The amount of weight the subjects exerted on the foot on the affected side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 8 publications
0
26
0
1
Order By: Relevance
“…This change is due to the advantage of the water environment, which reduces the stress on the joints through buoyancy, which counteracts the gravity felt by the human body on the ground, enabling movement with less force compared with the ground motion [27,28]. It is reported that such underwater gait training im-proves balance ability by increasing the stance phase and weight transfer ability of the affected side [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This change is due to the advantage of the water environment, which reduces the stress on the joints through buoyancy, which counteracts the gravity felt by the human body on the ground, enabling movement with less force compared with the ground motion [27,28]. It is reported that such underwater gait training im-proves balance ability by increasing the stance phase and weight transfer ability of the affected side [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we performed an aquatic exercise program including underwater gait training with these advantages [38]. Park et al [30] suggested that such underwater gait training is based on the improvement of stability of the lower extremity. Therefore, Jung et al [13] mentioned that applying additional weight was used to improve stability by minimizing the floatation of the lower limb.…”
Section: Discussionmentioning
confidence: 99%
“…Jung et al 9 conducted movement analysis after conducting aquatic treadmill training with affected side ankle weight load application as a cross-sectional study and as a result, during aquatic treadmill training with weight load application, compared to the control group, the weight load group showed increase of stability in the affected side lower limb. In the study by Park et al 29 there was a ter applying an additional weight load on the affected side ankle, and in the study by Regnaux et al 30 it was reported that an average of 6 cm/s gait speed improvement was represented after conducting contralateral side lower limb weight load treadmill gait training. In the movement analysis of aquatic gait training in the study by Barela et al, 31 it was reported at there was increase of muscle activity in the stance phase in the tensor fasciae latae muscle, vastus lateralis muscle, and biceps femoris muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke causes the psychological disorder with the and depending on the lesion site, the representative functional disorders of exercise, sense, gait, and balance, among which, disorders of gait and balance occur due to impairment of the motor and sensory nerves [5]. In addition, stroke patients tend to have difficulty performing tasks involving high positions, such as sitting, standing, walking, and stair climbing [6].…”
Section: Introductionmentioning
confidence: 99%